From Opposing of Styles to Aesthetic Eclectics – Linguistic Paradigm of Contemporary Life - Bartov, Arkadij (Respectus Philologicus, 2003)
This paper analyzes one of the principal characteristics of postmodernism and one of the main trends in the philosophy of modern art - ideological and aesthetic eclectics. The reasons of transition from confrontation of styles to stylistic eclectics in modern fiction and art are regarded. It is said that the fundamentals of modern eclectics take their source in the ideology of Soviet art, in Socialist Realism. Stylistic eclectics as a language paradigm of the present time is discussed while the style is being regarded as a language paradigm of the epoch, that is, the state of the language in this epoch.